Breaking Down the Barriers to a Natural Antiviral Agent: Antiviral Activity and Molecular Docking of Erythrina speciosa Extract, Fractions, and the Major Compound. Issue 2 (9th January 2020) - Fahmy, Nouran M.; Al‐Sayed, Eman; Moghannem, Saad; Azam, Faizul; El‐Shazly, Mohamed; Singab, Abdel Nasser
Abstract: The in vitro cytotoxic activity in Vero cells and the antiviral activity of Erythrina speciosa methanol extract, fractions, and isolated vitexin were studied. The results revealed that E. speciosa leaves ethyl acetate soluble fraction of the methanol extract (ESLE) was the most active against herpes simplex virus type 1 (HSV‐1). Bioactivity‐guided fractionation was performed on ESLE to isolate the bioactive compounds responsible for this activity. One sub‐fraction from ESLE (ESLE IV) showed the highest activity against HSV‐1 and Hepatitis A HAV‐H10 viruses. Vitexin isolated from ESLE VI exhibited a significant antiviral activity (EC50 =35±2.7 and 18±3.3 μg/mL against HAV‐H10 and HSV‐1 virus, respectively), which was notably greater than the activity of the extract and the fractions. Molecular docking studies were carried out to explore the molecular interactions of vitexin with different macromolecular targets. Analysis of the in silico data together with the in vitro studies validated the antiviral activity associated with vitexin. These outcomes indicated that vitexin is a potential candidate to be utilized commendably in lead optimization for the development of antiviral agents. Abstract :